Guía de Estrategias para Mejorar el Proceso de Enseñanza-Aprendizaje de Estudiantes con Síndrome de Asperger en la Unidad Educativa Leonardo Da Vinci. - Quelal Benavides, Angela Jhoana (2025)
The present research work aims to develop a guide of strategies to improve the teaching-learning process of students with Asperger Syndrome in the Leonardo Da Vinci Educational Unit”, it has been identified that the teachers of the institution do not provide meaningful learning to this type of population either by ignorance of the condition or also on how to work with these students. The teaching-learning process is based on active learning, motivation, sociocultural context, learning styles and rhythms, the use of innovative methodologies where the teacher is not only a transmitter of knowledge, but a mediator who facilitates learning experiences adapted to the cognitive and affective needs of the student. Students with Asperger Syndrome may show difficulties in the interpretation of social norms, the recognition of emotions in others, cognitive flexibility and adaptation to changes in routine, thus requiring a structuring of the environment and specific teaching. Based on this context, it can be mentioned that in many cases students with this condition are generally excluded from learning because teachers are not able to meet their needs. The study has a qualitative approach, with a non-experimental design, descriptive in nature, the population with which we worked were 12 teachers being a purposive sample selecting only those teachers who handle students with Asperger Syndrome, the technique used was the interview and its instrument was the interview guide. It is expected that with the implementation of the guide in the institution, teachers will have the tools to meet the needs of this type of students and be able to provide quality education and generate an inclusive environment in the classroom. Key words: Process, teaching, learning, Asperger Syndrome.